2016
DOI: 10.1160/th15-08-0687
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin: anti-inflammatory properties and clinical applications

Abstract: SummaryMany humoral and cellular components participate in bidirectional communication between the coagulation and inflammation pathways. Natural anticoagulant proteins, including antithrombin (AT), tissue factor pathway inhibitor, and protein C, suppress proinflammatory mediators. Conversely, inflammation blunts anticoagulant activity and, when uncontrolled, promotes systemic inflammation-induced coagulation, such as those that occur in disseminated intravascular coagulation and severe sepsis. This review dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 120 publications
0
61
1
Order By: Relevance
“…Second, differences between groups are likely to be statistically significant if the control event rate is high. Third, anticoagulants such as antithrombin and rhTM have specific anti-inflammatory activities unrelated to anticoagulant activity [ 30 32 ], and these anti-inflammatory effects might be clinically evident only in the severely ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, differences between groups are likely to be statistically significant if the control event rate is high. Third, anticoagulants such as antithrombin and rhTM have specific anti-inflammatory activities unrelated to anticoagulant activity [ 30 32 ], and these anti-inflammatory effects might be clinically evident only in the severely ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some anti-inflammatory actions of antithrombin are mediated by its anticoagulation action, whereas others are not [5,6]. …”
Section: The Mechanism Of Atiii Actionmentioning
confidence: 99%
“…antithrombin inhibits factor Xa-induced production of interleukin (IL)-6 and IL-8, as well as other molecules involved in monocyte recruitment and adhesion to endothelial cells [6]. …”
Section: The Mechanism Of Atiii Actionmentioning
confidence: 99%
“…In the present study, early heparin + antithrombin treatment significantly inhibited inflammation and suppressed the activities of caspase-3 and caspase-9 through the inhibition of NF-κB/p65 in the rabbit model of severe burns complicated by inhalation injury. Levy et al ( 16 ) also showed that antithrombin possesses noteworthy anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%